LEGALITAS PENGGUNAAN SMART CONTRACT BERBASIS BLOCKCHAIN DALAM PERJANJIAN BISNIS DIGITAL DI INDONESIA - Lourdes Fir Tondhi Sihotang; Silviani Silviani; Sri Handayani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The development of blockchain technology has given rise to new innovations in the legal and business fields, one of which is smart contracts. Smart contracts are digital agreements that are executed automatically based on program code without the need for a third-party intermediary. In digital business practices, the use of smart contracts offers efficiency, transparency, and transaction security. However, their implementation in Indonesia still raises legal issues, particularly regarding legality and legal certainty. This study aims to analyze the legality of using blockchain-based smart contracts in digital business agreements in Indonesia. The research method used is normative juridical with a statutory and conceptual approach. The results show that smart contracts can, in principle, be recognized as valid agreements as long as they meet the requirements for valid agreements and the provisions of electronic agreements under Indonesian law. However, specific regulations are needed to provide more comprehensive legal certainty.